Trends in the Management and Outcomes of Kidney Transplantation for Autosomal Dominant Polycystic Kidney Disease. (3rd August 2014) - Patel, Madhukar S.; Kandula, Praveen; Wojciechowski, David; Markmann, James F.; Vagefi, Parsia A.
Abstract : Background. Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic disorder leading to end-stage renal failure. The objective of this study was to evaluate a longitudinal experience of kidney transplantation for ADPKD. Methods. A single center retrospective review of patients undergoing kidney transplantation was conducted, with comparisons across two time periods: early (02/2000–04/2007, n = 66 ) and late (04/2007–08/2012, n = 67 ). Results. Over the 13.5-year study period, 133 patients underwent transplantation for ADPKD. Overall, no significant difference between the early and late group with regard to intraoperative complications, need for reoperation, readmissions within 30 days, delayed graft function, and mortality was noted. There was a trend towards increase in one-year graft survival (early 93.1% versus late 100%, P = 0.05 ). In the early group, 67% of recipients had undergone aneurysm screening, compared to 91% of recipients in the late group (P < 0.001 ). Conclusions. This study demonstrates consistent clinical care with a trend towards improved rates of one-year graft survival. Interestingly, we also note a significantly higher use of cerebral imaging over time, with the majority that were detected requiring surgical intervention which may justify the current practice of nonselective radiological screening until improved screening criteria are developed.